PENGARUH DIVIDEND PAYOUT TERHADAP VOLATILITAS HARGA SAHAM DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERATING - Vallerie, Silvia; Imelda, Elsa (Jurnal Paradigma Akuntansi, 2025)
Based on the research objectives to show the effect and interaction of dividend payout ratio on stock price volatility, and whether foreign ownership and domestic ownership can strengthen the connection of dividend payout ratio to stock price volatility in companies listed on the LQ45 index that have been registered in the 2019-2021 range in IDX list. The sample was selected by a purposive sampling method and as many as 25 companies were involved. The data obtained was processed by moderating regression analysis and multiple regression analysis supported by the E-views 12 and Microsoft Excel 2021 programs. This study showed that there was no significant relationship between the dividend payout ratio and stock price volatility. Foreign ownership and domestic ownership are not proven to strengthen the relationship between dividend payout ratio and stock price volatility. However, there is a significant relationship between earnings volatility and stock price volatility. This study aims to find factors that impact stock price fluctuations that can provide positive signals to investors for investment decisions.